Designing a good manufacturing practices (GMP) certified manufacturing unit for halal products in Gambang - Muhammad Azim, Rozali (2012)
An industry is a most important aspect in order to increase the economic status.Industry can also define as a basic category of business activity. Therefore,it is a need for Gambang area to have one industry based on HALAL product due to development of population.This paper is written out to design a Good Manufacturing Practices (GMP) certified manufacturing unit for halal products in Gambang.For pharmaceutical manufacturing unit,there are some requirements for complimentary medicines. They are quality management,personnel,premises & equipment, documentation, production,quality control,contract manufacture & analysis,complaints & recall and self inspection.The GMP scheme contains requirements and conditions for the safety of the manufacturing unit besides ensure the quality of the product.A standard GMP manufacturing unit has many benefits.Firstly,the GMP manufacturing unit can supply medical needed in a very large quantity.Secondly,the standardize from GMP regulation will provide a quality product that will ensure the health of people.Third, there will be a lot of job to be fulfilled by people in order to reduce unemployment problems in Malaysia.This GMP manufacturing unit can be done by two methods.First is by doing research and second is by doing industrial visit to get real surrounding of an industry.This research is very suitable to be done in Malaysia based on demanding on pharmaceutical needed.In order to reduce our dependence on other country for supplying the medical needed, we should have ours. Hence,a GMP manufacturing unit is the most suitable to accommodate out medical needed.